Surgical Correction of Kyphosis in Patients With Camptocormia Associated With Parkinson’s Disease: A Case Report and Review of the Literature - Mei, Guo-long; Wei, Hui-ting; Ma, Yue-rong; Wan, Dun (Frontiers in Surgery, 2022)
Background: Camptocormia is a postural deformity, which characterized by markedly flexed thoracic cage and lumbar spine. The symptoms are alleviated while walking and lying. Here we report a case of camptocormia which cause of Parkinson’s disease. Case description:A 70-year-old male presented with a fall injury causing low back pain for 3 months, aggravated for 2 months. He was diagnosed with a compression fracture after the injury and underwent PKP surgery at a local hospital, and had a 7-year history of Parkinson's disease. The MRI scan showed ununited L1 vertebrae and compression fracture of L2 vertebrae.The patient underwent canal decompression, and internal fixation of the T10-L3 intervertebral plate with bone graft fusion surgery in our hospital. Postoperatively, the lumbar lordosis was corrected and sensation was restored in both lower extremities. One month after the operation, the fixation was loosened, and a revision surgery was performed in our hospital. At the present follow-up of 1.5 years, the patient is in good general condition, not complaining of low back discomfort, actively exercising according to the rehabilitation treatment, and adapting well to society. Conclusion:This case illustrates a rare case of camptocormia in Parkinson's and highlights the need for careful evaluation of whether internal spinal fixation surgery is beneficial in such patients.